Comparison of tissue-interface pressure in healthy subjects lying on two trauma splinting devices: The vacuum mattress splint and long spine board. Issue 8 (August 2016) - Pernik, Mark N.; Seidel, Hudson H.; Blalock, Ryan E.; Burgess, Andrew R.; Horodyski, MaryBeth; Rechtine, Glenn R.; Prasarn, Mark L.
Abstract: Background: Most emergency transport protocols in the United States currently call for the use of a spine board (SB) to help immobilize the trauma patient. However, there are concerns that their use is associated with a risk of pressure ulcer development. An alternative device, the vacuum mattress splint (VMS) has been shown by previous investigations to be a viable alternative to the SB, but no single study has explicated the tissue-interface pressure in depth. Methods: To determine if the VMS will exert less pressure on areas of the body susceptible to pressure ulcers than a SB we enrolled healthy subjects to lie on the devices in random order while pressure measurements were recorded. Sensors were placed underneath the occiput, scapulae, sacrum, and heels of each subject lying on each device. Three parameters were used to analyze differences between the two devices: 1) mean pressure of all active cells, 2) number of cells exceeding 9.3 kPa, and 3) maximal pressure (Pmax ). Results: In all regions, there was significant reduction in the mean pressure of all active cells in the VMS. In the number of cells exceeding 9.3 kPa, we saw a significant reduction in the sacrum and scapulae in the VMS, no difference in the occiput, and significantly more cells above this value in the heels of subjects on the VMS. Pmax was significantly reduced in all regions, and was less than half when examining the sacrum (104.3 vs. 41.8 kPa, p < 0.001). Conclusion: This study does not exclude the possibility of pressure ulcer development in the VMS although there was a significant reduction in pressure in the parameters we measured in most areas. These results indicate that the VMS may reduce the incidence and severity of pressure ulcer development compared to the SB. Further prospective trials are needed to determine if these results will translate into better clinical outcomes.